SISTEM PENDUKUNG KEPUTUSAN PENGEMBANGAN FASILITAS PENUNJANG WISATA DI KABUPATEN PACITAN - Andi Kurniawan; Amir Hamzah; Naniek Widyastuti (Jurnal SCRIPT, 2016)
Pacitan is one of the areas favorite by tourists because it has many locations tourism very interesting . Many tourism into consideration to do the development of facilities in tourism undeveloped . With the support system decisions can give solution to tourism selection needs to be developed. This system designed by using the method simple additive weighting ( saw ) which is one of a method of fuzzy multiple attribute decission making ( fmadm ) .A method of saw chosen because it produces accurate results , and in the calculation of the weighting criteria is not too complicated. System is expected to help work the department of cultural tourism of youth and sports kabupaten pacitan , especially in the plane of development tourism in doing selection tourism improved and needs to be developed.